Adult airway management in ICU and regular floors: A prospective study as part of a healthcare improvement initiative in a tertiary care center - Carine Zeeni; Mohamed Al Jazzar; Wissam Maroun; Thuraya HajAli; Marc Moukarzel; Rawad Jamaleddine; Patrick Maroun; Marie T. Aouad (PLoS ONE, 2026)
Background Despite recent advancements, airway management outside the operating room (OR) remains a challenging task and is associated with a high rate of complications. The first pass success rate at our institution was low. We developed a standardized multidisciplinary protocol to improve it as part of a healthcare improvement initiative. Methods Following the implementation of the protocol, this prospective observational study was conducted on patients over 18 years old requiring intubation by anesthesia providers on regular floors and in intensive care units. The primary outcome was the first-attempt success rate of endotracheal intubation. Secondary outcomes included total number of attempts, time to successful intubation, equipment and medications used, and occurrence of adverse events such as severe hypotension (systolic blood pressure (SBP) ≤80 mmHg), severe hypoxemia (SpO2 ≤ 85%), and cardiac arrest. Results All 199 patients were successfully intubated, with 184 patients (92.5%) intubated at first attempt. Twenty-four patients had a baseline SBP ≤ 80 mmHg, with 35 additional patients experiencing a drop in blood pressure during intubation. Thirty-eight patients had a baseline SpO 2 ≤ 85%, with 11 additional patients experiencing desaturation during intubation. Two patients had cardiac arrest during intubation and were resuscitated. Multivariable logistic regression identified SpO2 ≤ 85% as the only predictor of hypoxemia (OR: 22.85, 95%CI: 9.07–57.55, P < 0.001) and baseline hypotension as the only predictor of hypotension during intubation (OR: 32.43, 95%CI: 7.14–147.33, P < 0.001). Conclusion Implementing a standardized multidisciplinary protocol that includes highly experienced anesthesia providers and the use of muscle relaxants resulted in a very high first-attempt intubation success rate in critically ill patients, with the persistence of a high incidence of adverse events. Our successful approach may inform other policymakers about best practices for safe intubation in high-risk patients, highlighting the need for strategies to mitigate hemodynamic and respiratory complications and encouraging them to implement airway healthcare improvement initiatives in their institutions.